The design and discovery of lixisenatide for the treatment of type 2 diabetes mellitus. (October 2014) - Christensen, Mikkel; Miossec, Patrick; Larsen, Bjarne Due; Werner, Ulrich; Knop, Filip K
<x xml:space="preserve">Abstract</x> Introduction: Lixisenatide is a once-daily short-acting glucagon-like peptide-1 (GLP-1) receptor agonist (GLP-1RA) used in the treatment of type 2 diabetes mellitus (T2DM). It is used in combination with oral antidiabetics and/or basal insulin in patients inadequately controlled on these medications and who are undergoing diet and lifestyle modification. GLP-1RAs glucose-dependently increase insulin secretion, decrease glucagon secretion, and slow gastric emptying, thereby improving glycemic control. GLP-1RAs are associated with body weight benefits and low rates of hypoglycemia which are welcome in patients with T2DM. Areas covered: The authors describe the identification of GLP-1RAs as suitable targets for modification with structure-inducing probe technology to improve stability and resistance to proteolytic degradation. Clinical studies have assessed lixisenatide across > 5000 patients as a monotherapy or add-on to a variety of commonly used antidiabetic medications. These studies highlighted the effects of lixisenatide on gastric emptying, explaining its particular improvements in postprandial plasma glucose (PPG) excursions and underscoring its efficacy in combination with insulin glargine. Lixisenatide was well tolerated, with nausea and vomiting being the most frequently reported adverse events. Expert opinion: The once-daily administration of lixisenatide as well as its substantial sustained effect on gastric emptying and, hence, PPG excursions are all important features compared with the other GLP-1RAs. The combination of two injectables, such as basal insulin to lower fasting plasma glucose and a GLP-1RA that curtails PPG excursions, is clinically valuable and could differentiate lixisenatide from other GLP-1RAs, especially from those continuously acting GLP-1RAs with little effect on gastric emptying and PPG excursions.